The Effect of Extrovert and Introvert Students on their Speaking Achievement - Rona Laili Ulil Ishlah; Alfan Zuhairi; Dzul Fikri (Jurnal Penelitian, Pendidikan, dan Pembelajaran, 2019)
This research was aimed to find out the comparison between extrovert and introvert students in their speaking ability. This research used quantitative method which analyzed using t-test. The writer used the questionnaire and students’ speaking score as the instrument. The subjects of this research were the fourth semester English department students in University of Islam Malang which total sample were 32 students. The finding of this study showed that students who had extrovert personality had better speaking ability than introvert students. It was proven from the t-critical value with df30 at the level of significance 0.05 was 2.042 whereas the t-value was 5.924. It can be concluded that extrovert students had better speaking than introvert ones.